Upaya Meningkatkan Kualitas Baca Qur’an Siswa Melalui Metode IQRA di TPQ Syuhada Kota Bengkulu - Mifta Apriliah; Islamiah Istikharah; Ahmad Ilham (Yayasan Darussalam Bengkulu, 2025)
Islamic Religious Education (PAI) plays a crucial role in shaping children's character and spirituality from an early age, particularly through the ability to read the Qur'an. However, based on national survey results and observations at TPQ Syuhada in Bengkulu City, children's Qur'anic reading skills remain low, as indicated by hesitant reading, inaccurate pronunciation, and improper intonation. In fact, the IQRA method is known as an effective, gradual, and systematic approach to teaching Qur'anic reading. This study aims to describe the efforts of Community Service Program (KKN) students in optimizing the IQRA method to improve Qur'an reading skills among TPQ students. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation. The results show that the active involvement of KKN students through mentoring, the use of varied methods, and motivational support has a positive impact on the improvement of children's Qur'anic reading quality. Challenges such as limited time and resources were addressed through creative and adaptive approaches. These findings contribute to the development of Qur'anic learning in TPQ and the implementation of religion-based KKN programs.